Enhancing Iron Separation and Recovery from Egyptian Banded Iron Formation Using Paper Industry Sludge: A Sustainable Reduction Roasting Approach (Rudarsko-geološko-naftni zbornik, 2025)
This paper proposes an innovative method to upgrade Um Nar Banded Iron Formation (BIF). The method consists of three stages: reduction roasting using paper industry sludge and sawdust, sulfuric acid leaching, and magnetic separation. The effects of CaCO3/sawdust concentration and magnetic field intensity were examined. This approach not only provides an effective means of processing complex and low-grade iron ores but also offers a sustainable solution for recycling industrial waste. Additionally, it utilizes biomass sawdust as a green reducing agent, a new type of clean energy source with low sulfur content, which does not pollute the environment. Adding paper industry sludge as calcium carbonate (CaCO3) led to its reaction with Si and Al minerals, forming grossular (Ca3Al2(SiO4)2(OH)4). This prevented SiO2 from reacting with iron oxides, thereby enhancing iron recovery. The resulting iron concentrate meets the quality standards necessary for steel production. The iron concentrate obtained through this method, i.e. reduction roasting conducted with 10% dosage of reductant, followed by acid leaching and magnetic separation at 2000 gauss, contains 67.23% total Fe and 1.5% SiO2 with a total Fe recovery of 73.82%, meeting the iron ore quality requirements of the steel and iron industry.